Community wells to mitigate the arsenic crisis in Bangladesh - van Geen Alexander; Ahmed K.M; Seddique A. A.; Shamsudduha M. (The World Health Organization, 2003)
OBJECTIVE: To monitor the effectiveness of deep community wells in reducing exposure to elevated levels of arsenic in ground-water pumped from shallower aquifers. METHODS: Six community wells ranging in depth from 60 m to 140 m were installed in villages where very few of the wells already present produced safe water. By means of flow meters and interviews with villagers carrying water from the community wells, a study was made of the extent to which these were used during one year. The results were compared with household and well data obtained during a previous survey in the same area. FINDINGS: The mean arsenic concentration in water pumped from wells already in use in the villages where the community wells, were installed was 180 ± 140 µg/l (n = 956). Monthly sampling for 4-11 months showed that arsenic levels in groundwater from five of the six newly installed wells were consistently within the WHO guideline value of 10 µg/l for drinking-water. One of these wells met the Bangladesh standard of 50 µg/l arsenic but failed to meet the WHO guideline values for manganese and uranium in drinking-water. The community wells were very popular. Many women walked hundreds of metres each day to fetch water from them. On average, 2200 litres were hand-pumped daily from each community well, regardless of the season. CONCLUSION: A single community well can meet the needs of some 500 people residing within a radius of 150 m of it in a densely populated village. Properly monitored community wells should become more prominent in campaigns to reduce arsenic exposure in Bangladesh. Between 8000 and 10 000 deep community wells are needed to provide safe water for the four to five million people living in the most severely affected parts of the country.